The Effect of Project-Based Learning on Students’ Mathematical Communication Skills - Salama, Umi; Fajriana, Fajriana; Elisyah, Nur (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
The low level of students’ mathematical communication skills in mathematics learning is caused by a learning process that is still teacher-centered. Therefore, a more student-centered learning model is needed, one of which is the project-based learning model as an alternative solution. This study was conducted to determine the effect of the project-based learning model on students’ mathematical communication skills. This study employed a quasi-experimental approach using a nonequivalent pretest-posttest control group design. All 10th grade classes were the research population. The sample was taken using purposive sampling, where X-2 was used as the experimental class and X-3 was used as the control class. Data was obtained by administering a test instrument to students. To test the hypothesis, the researcher used the Shapiro-Wilk normality test and the Mann-Whitney test, assisted by SPSS software version 26. Based on the results of hypothesis testing using the Mann-Whitney test, the Asymp. Sig. (2-tailed) value was 0,000 (≤ 0,05), resulting in the rejection of H0, concluding that there is an effect of the PjBL model on students' mathematical communication skills.